Heavy and light chain pairing of bivalent quadroma and knobs-into-holes antibodies analyzed by UHR-ESI-QTOF mass spectrometry. Issue 1 (2nd January 2016) - Schaefer, Wolfgang; Völger, Hans R; Lorenz, Stefan; Imhof-Jung, Sabine; Regula, Jörg T; Klein, Christian; Mølhøj, Michael
Abstract : The quadroma antibody represents the first attempt to produce a bispecific heterodimeric IgG antibody by somatic fusion of 2 hybridoma cells each expressing monoclonal antibodies with distinctive specificities. However, because of random heavy and light chain pairing, the desired functional bispecific antibody represents only a small fraction of the protein produced. Subsequently, the knobs-into-holes (KiH) approach was developed to enforce correct heavy chain heterodimerization. Assuming equimolar expression of 4 unmodified chains comprising 2 heavy and 2 light chains, the statistical distribution of all paired combinations can be calculated. With equimolar expression as the goal, we transfected HEK cells with 1:1:1:1 plasmid ratios and analyzed the protein A affinity-purified antibodies from the quadroma and KiH approaches qualitatively and quantitatively with regard to the estimated relative amounts of the products using electrospray quadrupole time-of-flight mass spectrometry. Our results show that all expected species are formed, and that, within the methodological limits, the species distribution in the mixtures corresponds approximately to the statistical distribution.